Metacommunity Structures of Macroinvertebrates and Diatoms in High Mountain Streams, Yunnan, China - Kurthen, Angelika L.; He, Fengzhi; Dong, Xiaoyu; Maasri, Alain; Wu, Naicheng; Cai, Qinghua; Jähnig, Sonja C. (Frontiers in Ecology and Evolution, 2020)
The metacommunity concept has received increasing interest in the past two decades. However, there has been limited research examining metacommunity structure of communities in high mountain streams. These ecosystems are often physically constrained and can display large environmental gradients within a relatively small spatial extent. Here, we examined metacommunity structures of stream organisms in a high mountain region, which is part of the Hengduan Mountains region in the Southwest China. Macroinvertebrates and diatoms were collected from six streams in two opposite aspects of the same mountain with different connectivity between streams. On the west aspect, streams are tributaries of a river (i.e. river-connected) while streams flow into a lake (i.e. lake-connected) on the east aspect. We used Elements of Metacommunity Structure analysis to explore the metacommunity structuring of these two biological models. We also compared the contribution of dispersal and environmental filtering in structuring metacommunities by looking at Euclidean, network, topographic, and environmental distances. Communities of diatoms and macroinvertebrates were structured with clear turnover on both aspects. Further, diatom communities exhibited Clementsian structure on both aspects. Macroinvertebrates exhibited different metacommunity structures on the river-connected aspect (Quasi-Clementsian) and lake-connected aspect (Clementsian). Our results indicated that on the lake-connected aspect, environmental filtering had a stronger association with community dissimilarity than on the river-connected aspect for both macroinvertebrate and diatom communities. Diatom communities were more influenced by environmental filtering on the east aspect with weakened network connectivity compared with those on the west aspect. Our results also emphasized the potential effects of biotic interactions between macroinvertebrates and diatoms on shaping community structures of one other. Given that high mountain streams are scarcely examined, our study provides substantial elements to further understand metacommunity structure and highlights the necessity of future research to reveal the underlying mechanisms of community structuring in these remote ecosystems.